Association of abruptio placentae with hypertension in pregnancy: Analysis of risk factors in Nigerian women - Maradona Isikhuemen; Lorretta Ntoimo; Vivian Onoh; Nosakhare Idiagbonya; Michael Orhue; Friday Okonofua (Reproductive, Female and Child Health)
Abstract Objective The incidence of abruptio placentae complicating hypertensive diseases of pregnancy is high in Nigerian referral hospitals. We conducted a retrospective case‐control study to identify the socio‐demographic, behavioural, and clinical risk factors associated with abruptio placentae in women with hypertensive diseases of pregnancy. Methods The 41 cases of hypertensive diseases complicated by abruptio placentae identified in the records of the University of Benin Teaching Hospital over 2 years (January 2021–December 2022) were compared with 208 women (controls) who had hypertensive diseases without developing abruptio placentae. Multiple regression analysis was used to develop maximum likelihood estimates of the adjusted odds ratios and 95% confidence intervals to predict the likelihood of the association between the exposure factors and the risk of abruptio placentae. Results High blood pressure levels at presentation, when managed, can decrease the odds for abruptio placentae by 9% OR 0.91, CI:0.83–0.9, but smoking and alcohol intake were not significantly associated with abruptio placentae. A higher haemoglobin concentration decreased the likelihood of abruptio placentae by 60% OR 0.40, (CI 0.24– 0.68), while higher birth weight babies minimally decreased the odds for abruptio placentae, OR 1.01 (CI 0.08–12.49). Conclusion We conclude that abruptio placentae is most likely to complicate hypertensive diseases of pregnancy in Nigerian women when there are concurrent pregnancy anaemia and low birth weight babies, while higher blood pressure levels at presentation, when promptly managed, can reduce the risk of abruptio placentae. Efforts to address the concurrent management of anaemia associated with hypertensive diseases in pregnancy will most likely reduce the incidence of abruptio placentae in this population.